True friendship : Geoffrey Hill, Anthony Hecht, and Robert Lowell under the sign of Eliot and Pound - Ricks, Christopher, 1933- (Anthony Hecht lectures in the humanities., 2010)
"True Friendship looks closely at three outstanding poets of the past half-century - Geoffrey Hill, Anthony Hecht, and Robert Lowell - through the lens of their relation to their two predecessors in genius, T.S. Eliot and Ezra Pound."--Inside jacket